(untitled) (Research, Society and Development, 2021)
Breadfruit (Artocarpus altilis) is described as an important food source in the diet of several countries, being considered as a valuable food with the potential to positively impact food security in the world. Breadfruit is a fruit of Asian origin with considerable economic and food importance for the region, due to its exceptional nutritional characteristics that bring benefits to the health to its consumers. However in Brazil, the fruit is little known and is underused. Only a very few scientific publications emphasizing the technological characteristics of breadfruit processing have been reported in the literature, which motivated the realization of the present research on its physicochemical characteristics. The fruits used were obtained from domestic orchards at the ripe and “green” ripening stages. The analyses performed were of pH, total soluble solids, total titratable acidity, water activity, ash content, lipids, protein, moisture and color (L*, a*, b*, C* and ºHue). Antioxidant activity through ABTS, DPPH and FRAP assays, and total phenolics and flavonoids compounds were determined. Descriptive data were analyzed by Analysis of Variance (ANOVA), Tukey mean test (p<0.05). The results of the physicochemical analysis indicated that the drying to obtain breadfruit flour is a viable alternative, which provides a nutritional increase and a more attractive color to the product, minimizes post-harvest losses, in addition to being a technology with high potential for the availability of new food alternatives. Comparing the two extracts, the antioxidant activity was higher in the ethanol extracts of breadfruit flour. This result may be related to the maturation stage and the concentration of its components. For the phenolics and flavonoids bioactive compounds, there was a significant difference (p<0.05), evidencing the aqueous extract, when compared to ethanolic extract.